Push-Pull Zinc Porphyrins as Light-Harvesters for Efficient Dye-Sensitized Solar Cells - Lu, Jianfeng; Liu, Shuangshuang; Wang, Mingkui (Frontiers in Chemistry, 2018)
Dye-sensitized solar cell (DSSC) has been attractive to scientific community due to its eco-friendliness, ease of fabrication, and vivid colorful property. Among the various sensitizers, such as metal-free organic molecules, metal-complex, etc, porphyrin is one of the most promising sensitizers for DSSC. The first application of porphyrin for sensitization of nanocrystaline TiO2 can be traced back to 1993 by using [tetrakis(4-carboxyphenyl) porphyrinato] zinc(II) with an overall conversion efficiency of 2.6%. More than 10 years later, Officer and Grätzel improved this value to 7.1%. Later in 2009, by constructing porphyrin sensitizer with an arylamine as donor and a benzoic acid as acceptor, Diau and Yeh demonstrated that this donor-acceptor framwork porphyrins could attain remarkable photovoltaic performance. Now the highest efficiencies of DSSC are dominated by donor-acceptor porphyrins, reaching a remarkable value of 13.0% with cobalt-based electrolytes. The key to this achievement is largely contributed from the structural development of donor and acceptor groups within push-pull framwork. In this review, we summarized and discussed the developement of donor-acceptor porphyrin sensitizers and their application in DSSC. A dicussion of correlation between molecular structure and the spectral and photovoltaic properties is the major target in this review, deeply dicussion of the substitution group, especially on porphyrin’s meso-position were summarized and discussed.